Experimental determination of kinetic constants, stoichiometric coefficients, nitrogen content and heavy metals in an activated sludge pilot plant - Morón, Oleyda; Torres, Trina; Morón Fuenmayor, Oneida (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
An activated sludge pilot plant, made up of four (4) aeration tanks and a secundary clarifier, was set up to compare the values of kinetic constants (K,Ks,Ko) and stoichiometric constants (Y,Kd,a,b) with those obtained in laboratory scale experiments and in the literature. Nitrogen content and heavy metals were also determined. The experiment lasted 22 days. When the results were compared, it was found that the maximum specific growth Ko, was lower (2,46 1/d) than the COD and larger than the BOD (1,62 1/d) with respect to the laboratory scale experiments but within the range reported in the literature. Specific growth constants K. COD and DBO were larger than both the laboratory scale and the literature. For the kinetic growth Ks, the COD was smaller (47,26 mg/1) and the BOD was larger (22,23 mg/1) than the results, respectively, and within the range of the literature data. With respect to COD and BOD, comparison showed that Kd, the endogenous decay coefficient, was lower: 0.058 1/d and 0.014 1/d, respectively. For the sludge production coefficient Y, the COD and the BOD were all lower (0,18;0,23). For the coefficient of oxygen demand COD was larger (0.11) than the laboratory scale results while BOD was larger (0,16) than the laboratory scale results. For the coefficient of oxygen demand b (0,025 mgO2/mgVSS) the COD was lower than the laboratory scale experiment and the literature data and the BOD was higher than the laboratory scale experiment. The values for ammonium nitrogen and nitrate were both within the literature range Heavy metals in water were found in trace quantities. A sludge age of 15 days is recommended since it provided better percentage removal with respect to COD and BOD.